2020
DOI: 10.1093/noajnl/vdaa004
|View full text |Cite
|
Sign up to set email alerts
|

T2/FLAIR-mismatch sign for noninvasive detection of IDH-mutant 1p/19q non-codeleted gliomas: validity and pathophysiology

Abstract: Background This study aimed to assess the validity and pathophysiology of the T2/FLAIR-mismatch sign for noninvasive identification of isocitrate dehydrogenase (IDH)-mutant 1p/19q non-codeleted glioma. Methods Magnetic resonance imaging scans from 408 consecutive patients with newly diagnosed glioma (113 lower-grade gliomas and 295 glioblastomas) were evaluated for the presence of T2/FLAIR-mismatch sign by 2 independent revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 27 publications
3
36
0
Order By: Relevance
“…The authors suggested that translation of this biomarker into a clinically applicable quantifiable prognostic measure would require extensive validation on larger datasets. 39 In contrast, our study introduces simple and automated image-based assessment of molecular markers which appears to be highly accurate ( IDH: specificity = 87.68%, sensitivity = 82.80%; 1p/19q-codeletion: specificity = 73.96%, sensitivity = 81.49%) of underlying molecular status.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The authors suggested that translation of this biomarker into a clinically applicable quantifiable prognostic measure would require extensive validation on larger datasets. 39 In contrast, our study introduces simple and automated image-based assessment of molecular markers which appears to be highly accurate ( IDH: specificity = 87.68%, sensitivity = 82.80%; 1p/19q-codeletion: specificity = 73.96%, sensitivity = 81.49%) of underlying molecular status.…”
Section: Discussionmentioning
confidence: 97%
“…Multiple recent studies have attempted to correlate T2–FLAIR mismatch with IDH and 1p/19q codeletion status in lower-grade gliomas. 38 , 39 For example, MRIs of 125 lower-grade gliomas from the TCIA dataset were evaluated by 2 independent neuroradiologists to assess for the presence/absence of T2–FLAIR mismatch sign. 38 All 15 cases declared positive by the readers for the T2–FLAIR mismatch sign were IDH -mutant 1p/19q-noncodeleted tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the T2–FLAIR mismatch sign could also have an important role in predicting the IDH status of gliomas, which may alter the extent of surgical removal of a glioma [ 16 , 19 ]. The purpose of our current study was to evaluate the presence of the T2–FLAIR mismatch sign in patients with LGG tumors, but also to evaluate the presence of this sign in high-grade tumors as well in a Greek cohort.…”
Section: Introductionmentioning
confidence: 99%
“…There are specific imaging features that correlate with altered metabolic processes of the tumor and thus contain the desired information. Examples are relative cerebral blood volume (rCBV) imaging 6 and mismatch of signal intensity distribution of T 2 w and FLAIR images (T 2 ‐FLAIR mismatch) 7 . Also, subtle imaging features of common diagnostic protocols may indicate the IDH mutation status.…”
mentioning
confidence: 99%